THE IMPLICATIONS OF RELIGIOUS MODERATION IN THE DIGITAL DA'WAH-BASED SOCIAL MEDIA FRAMEWORK FOR THE MILLENNIAL GENERATION (International Conference on Social and Islamic Studies, 2022)
In the era of completely open democracy, the differences in views and interests among citizens are very diverse, managed in such a way that aspirations can be conveyed properly. Massive information makes the public must be able to sort out the information they receive fairly and wisely. The presence of various developments in technology and information has become important in addressing the attitude of religious moderation. This study aims to find a model of the implications of religious moderation in the framework of digital da'wah-based social media, which is specifically for the millennial generation. Descriptive qualitative method used in this study, by taking literature sources that have a correlation with research problems such as journals, ebooks, websites and youtube. The results obtained are, to present or apply an attitude of moderation in the midst of the general public consisting of various cultures and beliefs, must be able to take a role in all matters related to religious social life. While the relation with digital da'wah to the millennial generation, essentially it will be more interesting if it is through social media, but it is also guided by the Islamic concept of Rahmatan Lil Alamin, which has implications for the attitude of religious moderation. An effective communication space dialogue for the millennial generation at home and in the community, will form a person who has character and becomes a tolerant character based on the philosophy of diversity in defending the NKRI, according to Islamic rules and government programs in religious moderation